Discussion on the Relevant Factors of General Surgery Incision Infection and Prevention Methods - Jin Baotao; Lv Changsheng; Kai Hu (MATEC Web of Conferences, 2017)
There are many reasons that can lead to incision infection of general surgical patients. The main reasons include weight, age, body albumin level, surgical time, observation ward, etc. This paper analyzes the clinic data of patients with incision infection after general surgery based on clinic practice and study on the reasons that have impact on general surgical incision infection and gives relevant prevention countermeasures.